Structure and Evolution of Islamic Insurance Studies: A 10-Year Bibliometrics Review - Chitra Yuliashri Katili; Rifadli D. Kadir; Nurul Fadhilah (el-Jizya: Jurnal Ekonomi Islam, 2025)
The investigation analyses the development and scientific framework of Islamic insurance research over the last decade, from 2015 to 2024. The study seeks to assess performance, delineate the scientific themes of Islamic insurance research, and enhance this subject by offering insights on areas for further development. This research integrates both databases, Scopus and Web of Science (WoS), employing RStudio and MS Excel to analyse 366 papers. The study revealed that activity in this field was primarily concentrated in Malaysia; the Journal of Islamic Accounting and Business Research was recognised as the principal source, with Khan designated as the most prominent author in this sector. Furthermore, four primary themes have emerged as focal points for scholars over the past decade, predominantly within the domains of business, management, economics, and social science. The four themes may be further elaborated upon in the future, and this research highlights aspects that have not been extensively explored. This research aims to offer significant insights for the advancement of research and the Islamic insurance sector in the future.